Perancangan Media Video Profil Guna Peningkatan Pelayanan Publik di Kantor Camat Danau Sipin Kota Jambi - Fitriani Fitriani; Emelia Jelita; Yerix Ramadhani (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Service to the community is the main objective in the implementation of public administration. In the implementation of public services, it must be based on service standards as a benchmark that is used as a guideline for service delivery and a reference for evaluating service quality as an obligation and promise of implementation to the community in the framework of quality, fast, easy, affordable and measurable services. The Danau Sipin sub-district office is one of the sub-district offices in Jambi City which provides public services in the field of population administration related to licensing and non-licensing. In the implementation of public services, there are problems regarding information management in terms of providing services in the form of information to the public. not yet effective and efficient or not yet digitized often makes it difficult for the community to obtain information regarding licensing or non-licensing requirements and procedures. Designing a video profile for the Danau Sipin Sub-district Office can improve information management in providing information services to the people of the Danau Sipin sub-district. The community can easily obtain information from social media such as YouTube which displays information related to licensing and non-licensing at the Danau Sipin Sub-district Office, Jambi City.